IMPLEMENTATION OF TA'WIDH ON PROBLEM FINANCING AT KSPPS BINA MITRA WAHANA AR-RAHMAH JATIM VIEWED FROM DSN-MUI FATWA NO 17/DSN-MUI/IX/2000 AND DSN-MUI FATWA NO 43/DSN-MUI/VIII/2004” - Oktaria Ardika Putri (Jurnal Ekonomi, 2022)
This study aims to explain how ta'widh is enforced on problem financing at KSPPS BMW Ar-Rahmah East Java and how ta'widh is enforced on problem financing at KSPPS BMW Ar-Rahmah East Java in terms of DSN-MUI fatwa No. 17/DSN-MUI/IX /2000 and DSN-MUI fatwa No. 43/DSN-MUI/VIII/2004. This research approach is descriptive qualitative. Methods of data collection using interviews, observation, and documentation. The results of this study are as follows: The implementation of ta'widh on troubled financing at KSPPS BMW Ar-Rahmah East Java, namely all adjustments as stipulated in the DSN-MUI fatwa where KSPPS will adjust to real losses. The ta'widh (compensation) implementation is set for members at 4% at the beginning of the contract and accumulates every day of delay. Furthermore, KSPPS BMW Ar-Rahmah East Java has implemented ta'widh according to the provisions of Fatwa No. 17/DSN-MUI/IX/2000, which does not give ta'widh to members who experience force majeure and impose sanctions on those who are proven capable and procrastinate, and funds from fines are used for social funds.